Sperm morphological abnormalities visualised at high magnification predict embryonic development, from fertilisation to the blastocyst stage, in couples undergoing ICSI - Setti, Amanda Souza (J Assist Reprod Genet, 2014)
PURPOSE: To investigate the predictive value of the motile sperm organelle morphology examination (MSOME) on embryo morphology. METHODS: The morphologies of 540 embryos obtained from 60 couples undergoing ICSI were evaluated from days 1 to 5 of development and were examined for associations with the percentages of morphologically normal paternal sperm and of the paternal sperm with large nuclear vacuoles (LNVs) as determined by MSOME. RESULTS: An increased percentage of LNV sperm was associated with increased odds of a zygote presenting with pronuclear abnormalities. It was also associated with decreased odds of (i) normal cleavage on days 2 and 3 of development, (ii) the presence of a high-quality embryo on day 3, (iii) the development of an embryo to the blastocyst stage, and (iv) an embryo possessing a normal trophectoderm and inner cell mass. The calculated areas under the curves differed for the embryos that did and did not develop to the blastocyst stage and for the high- and low-quality blastocysts. The optimal cut-off value for the percentage of LNV sperm that maximised proper blastocyst formation was ≤24.5 %, and the cut-off value that maximised blastocyst quality was ≤19.5 %. CONCLUSIONS: These results suggest a very early onset of paternal influences on embryo development. The evaluation of the incidence of vacuoles by MSOME may significantly improve upon the prognostic information provided by conventional semen analyses.